Karakteristik Daya Turbin Pelton Skala Mikro Dengan Variasi Perbandingan Jumlah Sudu dan Sudut Sudu - Halim Rivardi Thamrin; Antonius F A Silaen; Putra Bismantolo (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2020)
Abstract Pelton turbines are widely used for micro scale power plants, this research aims to study the performance of pelton turbines with blades from L bow paralon material used for power generation. The equipment used is a pelton turbine, turbine blade is made of paralon material with a width of 2.5 cm and a length of 8 cm and a height of 1.25 cm. runner diameter is 35 cm with a number of 8 blades and 16 blades. The study was carried out by varying the number of blades and the angle of blades and the flow rate with pump pressure with a slope angle of 750 and 900 and water pressure of 0.9 bar, 1.5 bar and 1.8 bar. To produce electricity, the turbine is connected to the alternator, the measurement of the power generated by the turbine is done by measuring the voltage and current generated by the generator. Pelton turbine with 8 blades with 1.8 bar pump pressure with 750 blades produces 7,343 watts of power with an efficiency of 87.18%, at an angle of 900 produces 7,06 watts of power and an efficiency of 89.11%. On the 16 blades with a pressure of 1.8 bar with an angle of 750 produces a power of 7.7418 watts with an efficiency of 91.98% and at a blade angle of 900 the power produced is 7.886 watts with an efficiency of 93.62%. So the greater the pump pressure and the greater the number of blades and blades, the greater the power and rotation of the turbine produced.